2019
DOI: 10.1111/petr.13568
|View full text |Cite
|
Sign up to set email alerts
|

Impact of standardized protocols for cytomegalovirus disease prevention in pediatric solid organ transplant recipients

Abstract: End‐organ disease caused by CMV is a significant cause of morbidity and mortality in pediatric SOT recipients. Pediatric transplant centers have adopted various approaches for CMV disease prevention in this patient population. We observed significant practice variation in CMV testing, prophylaxis, and surveillance across SOT groups in our center. To address this, we implemented evidence‐based standardized protocols and measured outcomes pre‐ and post‐implementation of these protocols. We performed retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
4
11
0
Order By: Relevance
“…No increase in CMV invasive disease was identified after modification of a local CMV prevention protocol which included earlier transition to oral valganciclovir, increased surveillance testing, and decreased use of CMVIG among high‐risk heart recipients. This is consistent with the findings from a recent study at another pediatric center …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…No increase in CMV invasive disease was identified after modification of a local CMV prevention protocol which included earlier transition to oral valganciclovir, increased surveillance testing, and decreased use of CMVIG among high‐risk heart recipients. This is consistent with the findings from a recent study at another pediatric center …”
Section: Discussionsupporting
confidence: 93%
“…In addition, the post‐intervention group's CMV infection rate was similar to that observed in previous pediatric studies . One recent study showed no increase in the CMV infection rate when comparing pre‐ and post‐standardized prophylaxis followed by surveillance . However, the current study introduces surveillance on prophylaxis with the presence of CMV infections occurring while on prophylaxis.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations